A Review of the Mechanism of Action of Cyclosporine A: The Role of Cyclosporine A in Dry Eye Disease and Recent Formulation Developments - Periman LM (Dove Medical Press, 2020)
Laura M Periman,1 Francis S Mah,2 Paul M Karpecki3 1Periman Eye Institute, Seattle, WA, USA; 2Scripps Health, La Jolla, CA, USA; 3Kentucky Eye Institute, Lexington, KY, USACorrespondence: Laura M PerimanPeriman Eye Institute, Seattle, WA, USAEmail dryeyemaster@gmail.comAbstract: Dry eye disease (DED) is a multifactorial disease of the ocular surface and tear film that has gained awareness as a public health problem. Characteristics of DED include tear film instability, hyperosmolarity, and ocular surface inflammation, which can occur independently or may be a sequela of numerous ocular diseases, ocular surgery or contact lens wear. Much has been learned about the impact of the disease to help affected individuals who report symptoms of poor vision, pain, and tearing. Recently, new research highlights the importance of the role of ocular surface inflammation and damage in DED—leading to a vicious cycle of inflammation as well as loss of tear film homeostasis. DED immunopathophysiology is characterized by four stages: initiation, amplification, recruitment, and re-initiation. Cyclosporine is proven to be a valuable ophthalmic therapeutic for DED through its immunomodulatory actions and regulation of the adaptive immune response. Cyclosporine mechanism of action is well described in the published literature and the myriad of benefits in all four stages lend a broad-based immunomodulatory function particularly suitable for addressing DED. Furthermore, cyclosporine has unique goblet cell density improvement capabilities as well as anti-apoptotic properties. Topical formulations of cyclosporine are centered around addressing the highly lipophilic nature of the molecule. The poor aqueous solubility of cyclosporine traditionally presented technical challenges in drug delivery to the ocular surface. Newer formulations such as cationic emulsions and nanomicellar aqueous solutions address formulation, tissue concentration, and drug delivery challenges.Keywords: dry eye disease, cyclosporine A, emulsion, OTX-101, keratoconjunctivitis sicca